The walking cure: Walk-along som undersøgelsesmetode til brugeroplevelser - Jantzen, Christian; Lykke, Marianne; Skov, Mette (Academic Quarter | Akademisk kvarter, 2019)
Experiences are seminal for human well-being. But experiencing is a complex phenomenon challenging standard methods of data collection. Firstly, experiencing is an inner process, which cannot be observed neither precisely nor in its totality from an external position. Observation studies therefore do not sufficiently account for this inner process. Secondly, experiences are dual: on the one hand, experiencing is bound to a stream of moments of sensing and perceptions, on the other hand experience is a recollection of such experiencing. Memory is a retrospective, but fallible representation of these moments. Interviews draw on and activate memory, but they fail to grasp the actual moments of experiencing. This paper presents the walk-along method as a way to deal with the complexity of experiencing. This method combines aspects of participatory observation and of interviewing as the researcher moves through space with the informants while they are moved by their surroundings.